1984
DOI: 10.1104/pp.76.4.918
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Effects on Potassium Fluxes by Northwest Coniferous Seedlings

Abstract: In ectomycorrhizae, the relative abilities of mycobiont and host plant to take up and store inorganic nutrients are not easily determined due to the intimate physical relationship of the two components forming the association. Since [Bong.j Carr.) seedlings.Mycorrhizas significantly increased 8'Rb uptake rates while decreasing the amount of MRb released to the external solution. Using compartmental analysis, the flux data suggest that the primary mycorrhizal effects were to increase inward potassium flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…1). Rygiewicz and Bledsoe (1984) reported that external hyphae in EM symbiosis have a high capacity to take up K + and deliver the nutrient to the host plant. In addition to stimulating K + uptake, P. involutus colonization benefits the salinized hosts by slowing down the rate of K + loss.…”
Section: Em Ameliorates K + Homeostasismentioning
confidence: 99%
“…1). Rygiewicz and Bledsoe (1984) reported that external hyphae in EM symbiosis have a high capacity to take up K + and deliver the nutrient to the host plant. In addition to stimulating K + uptake, P. involutus colonization benefits the salinized hosts by slowing down the rate of K + loss.…”
Section: Em Ameliorates K + Homeostasismentioning
confidence: 99%
“…Large amounts of K ϩ are, therefore, required for plant growth, and the availability of this cation is often limited in the absence of fertilization. In forest ecosystems, ectomycorrhizal symbiosis improves the whole mineral nutrition of the tree, including K ϩ nutrition (3,51). The fungal partner can explore large soil volumes and be very efficient in mobilizing and taking up K ϩ ions, which can thereafter be secreted toward the host plant.…”
Section: H Cylindrosporum As a Model Ectomycorrhizal Fungus-kmentioning
confidence: 99%
“…For example, George et al (1992), who examined the nutrient absorption by hyphae of Glomus mosseae found that this VA mycorrhizal fungus had no effect on K uptake. By contrast, Rygiewicz & Bledsoe (1984) found an enhanced K ()'Rb) uptake and storage in ectomycorrhizal roots due to higher uptake rates, an increase of vacuolar pool sizes and reduction of the K efflux.…”
Section: mentioning
confidence: 74%
“…These authors suggested that synthesis of organic acids by the fungi might be responsible for a higher availability of K in the soil. In conifers, the higher uptake of K by ectomycorrhizal associations has been attributed to increased influx rates, decreased efflux and an enhancement of the vacuolar pool (Rygiewicz & Bledsoe, 1984).…”
Section: mentioning
confidence: 99%